New scintillators for fast and thermal neutron detection - Galunov, N.Z.; Karavaeva, N.L.; Seminozhenko, V.P. (Functional Materials, 2012)
Proposed a technology to obtain a new class of detectors, namely organic composite scintillators. It allows us to create the scintillation detectors of an unlimited area. We consider hydrogen-bearing composite scintillators as the detectors of fast neutrons. The composite scintillators based on gadolinium silicate and pyrosilicate are discussed as the thermal neutron detectors. As well we consider the combined detector for selective detection of thermal and fast neutrons in the presence of background gamma radiation. Scintillation characteristics of the composite detectors are analyzed in comparison with the scintillation systems based on single crystals.